STEM Outreach via Science Forensic Module: The Impact of the Near-peer Mentoring Approach - Hazeeq Hazwan Azman; Maegala Nallapan Maniyam; Marini Ibrahim; Hasdianty Abdullah; Khairil Bariyyah Hassan; Hasnur Hidayah Kamaruddin; Rahayu Md. Khalid; Norhisyam Mat Sout; Norazah Mohammad Nawawi; Normawati@Nadzirah Abu Samah; Rozila Alias; Nor Suhaila Yaacob; Yusmi Mohd Yunus; Noraini Idris (Southeast Asian Mathematics Education Journal, 2019)
STEM education emphasizes the integrated study of science passing the boundaries of traditionally labelled disciplines while demonstrating its application in real life. Science forensic is an eye-catching subject for students, which implements the knowledge of biology, physics, and chemistry. The purpose of this study was to identify students’ interest towards STEM through science forensic module and the impact of the near-peer mentoring approach in the module for STEM outreach. This pilot study was conducted for the students of Sekolah Berasrama Penuh Integrasi (SBPI) Gombak with 36 participants. By using the Statistical Package for the Social Science (SPSS), the analysis revealed that 94.5% of students found the module interesting and 77% of participants agreeing that the module increased their interest to pursue their future study in the STEM-field. Focusing on demographics, this module received more positive responses from females and pure science stream students as compared to males and Islamic science stream, respectively. This result is consistent with the higher number of female students and pure science stream students in STEM-field study at university level. The near-peer mentoring approach showed a promising impact with 88% of students giving positive feedback on the credibility of mentors. The science forensic modules consisted of 8 main stations with the Fingerprinting station being the most popular (94.5%) and DNA profiling being the least popular (77.8%). One possible explanation of this is that the level of understanding for DNA profiling is harder with larger amounts of knowledge needed to be learned in a short period of time. Overall, the outcomes of this study suggest that exposing secondary school students to science forensic has a positive impact on their level of interest towards STEM education.